Epidemiology of childhood trauma and its association with insomnia and psychotic-like experiences in Chinese Zhuang adolescents - Wei, Qiaoyue; Pan, Yuli; Zhang, Shengjie; Yin, Wenwen; Lin, Qinghong; Pan, Shuibo; Dai, Chenyangzi; Zhou, Linhua; Wu, Junduan (Frontiers in Psychiatry, 2022)
Background: Adolescents who have experienced childhood trauma are more likely to have insomnia and psychotic-like experiences (PLEs) than adolescents from other ethnic groups. However, little is known about the youth of ethnic minorities. This study aimed to investigate the epidemiology of childhood trauma and its relationship with insomnia and PLEs in Chinese Zhuang adolescents, focusing on the role of specific trauma type and accumulation. Methods: A questionnaire of Childhood Trauma Questionnaire-Short Form (CTQ-SF), Athens Insomnia Scale (AIS), and Chinese Version Community assessment psychic experiences-8 (CCAPE- 8) were all completed by 1493 Chinese Zhuang adolescents. Chi-square and binary logistic regression analyses examined the association between childhood trauma and insomnia/PLEs. Results: The incidences of emotional abuse (EA), physical abuse (PA), sexual abuse (SA), emotional neglect (EN), and physical neglect (PN) occurred at rates of 5.63%, 5.02%, 6.56%, 23.98%, and 33.15%, respectively. EA, SA, EN, and PN were all positively related to insomnia (OR: 1.314–7.720, all p <0.05). EA and SA were positively associated with PLEs (OR: 2.131–3.202, all p <0.001). Adolescents who had experienced three or more types of traumas were more likely to have insomnia (OR=6.961, p <0.001) and PLEs (OR= 3.558, p <0.001). Conclusion: The most common type of childhood trauma is PN. Childhood trauma have the primary effect on insomnia/PLE. A significant dose-response relationship was found between Childhood trauma and insomnia/ PLEs.